Results of a randomized controlled trial to promote physical activity behaviours in mothers with young children - Monteiro, Ginny; Jancey, Jonine; Dhaliwal, Satvinder; Howard, P.; Burns, Sharyn; Hills, A.; Anderson, A. (Elsevier, 2014)
Objective: Increasing levels of physical activity in mothers have long-term health benefits for the mother and family. The study aimed to evaluate the effect of a six-month, physical activity RCT for mothers of young children. Methods: Women were recruited via playgroups and randomly assigned to intervention (n = 394) or control group (n = 322). The intervention group received a six-month multi-strategy programme delivered via playgroups in Perth, Australia. Measures were mean minutes per week of moderate (M) and vigorous (V) intensity physical activity (PA), and number of days/week of muscle strength exercises. Results: The intervention had a significant effect on mean time for vigorous (p = 0.008), moderate (p = 0.023) and total physical activity (p = 0.001) when compared to the control group. The intervention group increased their vigorous activity by a mean of 24 min/week, moderate activity by 23 min/week and total physical activity by 72 min/week. Conclusions: A relatively minimum home based intervention was able to demonstrate modest but statistically significant improvements in physical activity in a hard to reach group. These changes if maintained over a longer period are likely to improve the health of mothers and have a positive impact on their partners and children.